The Tawdry Tale of "Sheikh" Puji and Luftiana: Child Marriage and Polygamy in Indonesian Discourse - Woodward, Mark; Rochmaniyah, Inayah (Musawa Jurnal Studi Gender dan Islam, 2009)
This paper concerns the practice of, and discourse concerning child marriage and polygamy in contemporary Indonesia and the religious, social, and political contexts in which they are located. It focuses on the tale of Pujiono Cahyo Widayanto, who is more commonly knoum as Sheikh Puji, and his child bride Umi Hani Lutfiana Ulfa that has reverberated through the Indonesian media for more than a year. Sheikh Puji and Lutfiana have become icons in a high stakes symbolic and legal drama pitting socially and religiously conservative groups against progressive Muslims advocating reform of Islamic Family Law, the empowerment of women and modernity. Sheikh Puji has become an iconic figure in this struggle for three reasons: his flamboyant style, his defiant disregard and contempt for Indonesian civil law, and the fact he combines polygamy and child marriage in a single package.